15 Validation of fractal dimension of the incipient blood clot in stemi and stable coronary artery disease. (25th January 2018) - Sabra, Ahmed; Lawrence, Matthew James; Obaid, Daniel; Chase, Alexander; Smith, Dave; Thomas, Phillip; Hawkins, Karl; Williams, Phylip Rhodri; Morris, Keith; Evans, Phillip Adrian
Abstract : Background: Antithrombotics are the mainstay of management in coronary artery disease (CAD). However, no biomarker is available to assess their global effect on clot formation and structure. We validated a novel biomarker that measures clot microstructure, fractal dimension of incipient blood clot ( df ), in healthy volunteers, stroke, lung cancer and sepsis. Aims: To validate df in both acute and stable CAD, and assess the effect of therapeutic intervention. Methods: We prospectively recruited 2 groups: serial venous blood samples were collected on admission, after primary percutaneous coronary intervention (pPCI) and 24 hours in patients with STEMI, and a blood sample prior to angiography was obtained from 251 consecutive patients undergoing diagnostic coronary angiography. Patients were categorised based on angiographic findings as presence or absence of obstructive CAD (stenosis ≥50%). Results: In 38 STEMI patients, df after pPCI was lower than df on admission (mean 1.631±0.063 vs 1.751±0.052, p<0.000001) whereas df at 24 hour was similar to that on admission. For group 2, a significant difference in df was observed between obstructive CAD and unobstructive CAD (mean 1.748±0.057 vs 1.732±0.052, p 0.028), where patients with significant CAD produce denser, more tightly packed clots. Conclusions: We characterise clot microstructure, as measured by df, in patients with STEMI and stable CAD. df can potentially be used to risk-stratify patients with stable CAD and assess the efficacy of therapeutic interventions by measuring changes in clot microstructure.